Implementasi Pembelajaran Projek pada Sekolah Penggerak di Era Digital - Naning Hidayati; Dian Hidayati; Zusuf Hani Saputro; Tutik Lestari (Journal of Education and Teaching (JET), 2023)
The goal of this study is to discuss how project learning is being implemented at the driving school with a variety of obstacles to overcome and solutions to make it more efficient. This research uses case study method. Data collection techniques were conducted by interview, observation, and documentation. The data analysis technique uses the Miles and Huberman case study model. The results of the study show that project learning in this school has been carried out in two rounds in one year. In its implementation, several challenges were found, namely the incompatibility between group members, the lack of synchronization of the mindset between the central government and local governments, and financing in the implementation of project learning. The school's strategy to answer these challenges includes holding regular meetings between students, homeroom teachers, and BK teachers. In the meeting, reinforcement and motivation were given about the importance of working together. To make learning outcomes more appropriate for the learning environment, schools conduct independent assessments of the outcomes. At the start of the new school year, funds for student development are used to fund project activities.